PELATIHAN MANAJEMEN RANTAI PASOK PUPUK ORGANIK BAGI KELOMPOK TANI DEWI SRI DESA JAJAR GUMREGAH - lestari, Wahyu Dwi; Maulana, Hendra; Nuryananda, Praja Firdaus; Lestari, Mufida Diah (Universitas Mataram, 2024)
Good organic fertilizer supply chain management is essential to support the sustainability of agriculture in Indonesia, especially in rural areas. The Dewi Sri farmer group in Jajar Gumregah Village faces challenges in the distribution and stock management of organic fertilizer, which often impacts the productivity and quality of agricultural products. Improved knowledge and skills in supply chain management need to be trained, so that the distribution of organic fertilizer becomes more efficient, timely, and quality. The Organic Fertilizer Supply Chain Management Training for Dewi Sri Farmer Group in Jajar Gumregah Village aims to increase the capacity and efficiency of farmer groups in managing organic fertilizer production and distribution. Service activities involve several stages, starting from needs identification, program planning, training implementation, to evaluation and mentoring. Participants are given modules or practical guides as well as case studies to understand effective and efficient management of organic fertilizer distribution according to the needs of farmer groups. The results of the activities show that the implementation of effective supply chain management can increase the quality and quantity of organic fertilizer production, reduce operational costs, and improve the distribution system. Farmer group members gain new knowledge and skills in managing the supply chain more efficiently, which in turn supports increased agricultural productivity and economic welfare of the farming community. This service also contributes to the achievement of the Sustainable Development Goals (SDGs), particularly in ending hunger (SDG 2), promoting decent work and economic growth (SDG 8), and ensuring sustainable consumption and production patterns (SDG 12). This service underscores the importance of continuous training and technology application in agricultural supply chain management.